Poverty and Social Impact Analysis : Linking Macroeconomic Policies to Poverty Outcomes; Summary of Early Experiences - Kende-Robb, Caroline (Washington, D.C. : International Monetary Fund, 2003)
The objective of this paper is to present some early experiences of poverty and social impact analysis (PSIA) from the PRGF-supported programs in the African Department. The paper illustrates that many staff country reports have taken a first step toward PSIA by making more explicit the links between poverty and policies. Various examples highlight that even though relationships can be complex and analysis, as a result, may not be definitive, it is possible to assess some of the potential poverty effects even in countries with limited data, and therefore contribute to a more informed policy debate and design. The paper concludes that PSIA can help design policies that are more pro-poor, better define appropriate compensatory and complementary measures where appropriate, and support country ownership of reforms by promoting a public debate on trade-offs between policy choices. In light of this, the paper proposes that PRGF policy advice would benefit from more systematic PSIA and that staff country reports could report more on the potential policy trade-offs and poverty outcomes based on PSIA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet